Trichoderma for managing Lepidopteran insect pests: Current understanding and future directions - Reza Fauzi Dwisandi; Mia Miranti; Dedat Prismantoro; Mehrdad Alizadeh; Muhamad Shakirin Mispan; Wawan Hermawan; Zulqarnain Mohamed; Febri Doni; Ravindra Chandra Joshi (Biological Control, 2024)
Globally, Lepidopteran insect pests inflict substantial agricultural burdens, causing billions of dollars in losses annually. Synthetic pesticides are commonly employed to mitigate these losses. However, their use is associated with known environmental impacts, including the development of resistance in Lepidopteran pests. In response to this challenge, biological control methods utilizing the fungal genus Trichoderma have emerged as a promising eco-friendly alternative. Studies on the mechanisms underlying Trichoderma-mediated pest control have raised questions about its comparability to other entomopathogenic fungi. Our review reveals that Trichoderma not only uses traditional parasitism mechanisms or insect mummification but also relies on secondary metabolites it produces without parasitizing a host. This unique strategy positions Trichoderma as a highly promising tool in agriculture due to its multifunctional nature. This review highlights the potential of Trichoderma as a sustainable and environmentally friendly alternative to chemical pesticides for managing Lepidopteran insect pests.